First attempt to evaluate of burnout among school counselors after lifting pandemic rules in Indonesia - Itsar Bolo Rangka; M Ramli; Wahyu Eka Prasetyaningtyas (Universitas Negeri Padang, 2022)
The rate of burnout in school counselors is a critical issue in regulating individual work activities. This is a first and cross-sectional study that intends to examine the burnout of school counselors after the permitting of lifting due to the Covid-19 pandemic in Indonesia. It is reported that 188 school counselors in Jakarta, Bogor, Depok, Tangerang and Bekasi have filled out the Counselor Burnout Inventory to measure the burnout case they are dealing with. The data that has been raised was evaluated via the Rasch Model. The results of the study show that the rate of Burnout in school counselors has different statuses from each other, and highly depends on the demographic aspects investigated in this study. The study also verified that all school counselors were frustrated with their effectiveness as counselors. Nevertheless, counselors still promote their professionalism to advance the counseling services and promote the welfare of their clients. Discrepancies in the rate of school counselor burnout based on demographic aspects are also discussed in this article.